The caterpillar Manduca sexta brain shows changes in gene expression and protein abundance correlating with parasitic manipulation of behaviour - McMillan LEM; Herbison RH; Biron DG; A Barkhouse; DW Miller; N Raun; Adamo SA (Scientific Reports)
Abstract The parasitic wasp, Cotesia congregata, manipulates the behaviour of its host, the caterpillar Manduca sexta. The female wasp injects her eggs and a symbiotic virus (i.e. bracovirus, CcBV) into the body of its host. The host’s behaviour remains unchanged until the wasps exit the caterpillar, and then the caterpillar becomes a non-feeding “bodyguard” for the wasp cocoons. Using proteomic, transcriptomic and qPCR studies, we discovered an increase in antimicrobial peptide gene expression and protein abundance in the host central nervous system at the time of wasp emergence, correlating with the change in host behaviour. These results support the hypothesis that the wasps hyperactivate an immune-neural connection to help create the change in behaviour. At the time of wasp emergence, there was also an increase in bracoviral gene expression and proteins in the host brain, suggesting that the bracovirus may also be involved in altering host behaviour. Other changes in gene expression and protein abundance suggest that synaptic transmission may be altered after wasp emergence, and a reduction in descending neural activity from the host’s brain provides indirect support for this hypothesis.